Comprehensive Expression Profiling of Rice Tetraspanin Genes Reveals Diverse Roles During Development and Abiotic Stress - Mani, Balaji; Agarwal, Manu; Katiyar-Agarwal, Surekha (Frontiers in Plant Science, 2015)
Tetraspanin family is comprised of evolutionarily conserved integral membrane proteins. The incredible ability of tetraspanins to form ‘micro domain complexes’ and their preferential targeting to membranes emphasizes their active association with signal recognition and communication with neighboring cells, thus acting as key modulators of signaling cascades. In animals, tetraspanins are associated with multitude of cellular processes. Unlike animals, the biological relevance of tetraspanins in plants has not been well investigated. In Arabidopsis tetraspanins are known to contribute in important plant development processes such as leaf morphogenesis, root, and floral organ formation. In the present study we investigated the genomic organization, chromosomal distribution, phylogeny and domain structure of 15 rice tetraspanin proteins (OsTETs). OsTET proteins had similar domain structure and signature ‘GCCK/R’ motif as reported in Arabidopsis. Comprehensive expression profiling of OsTET genes suggested their possible involvement during rice development. While OsTET9 and 10 accumulated predominantly in flowers, OsTET5, 8, and 12 were preferentially expressed in root tissues. Noticeably, seven OsTETs exhibited more than twofold up regulation at early stages of flag leaf senescence in rice. Furthermore, several OsTETs were differentially regulated in rice seedlings exposed to abiotic stresses, exogenous treatment of hormones and nutrient deprivation. Transient subcellular localization studies of eight OsTET proteins in tobacco epidermal cells showed that these proteins localized in plasma membrane. The present study provides valuable insights into the possible roles of tetraspanins in regulating development and defining response to abiotic stresses in rice. Targeted proteomic studies would be useful in identification of their interacting partners under different conditions and ultimately their biological function in plants.